1985
DOI: 10.1007/bf01259439
|View full text |Cite
|
Sign up to set email alerts
|

Developmental puffing activity in the salivary gland and Malpighian tubule chromosomes ofAcricotopus lucidus (Diptera, Chironomidae)

Abstract: Abstract.A detailed map of the salivary gland chromosomes of Acricotopus lucidus is presented. Differences in puffing and developmental puffing sequences of the three salivary gland lobes were investigated from mid fourth larval instar to pupation and compared with the puffing pattern of the Malpighian tubules. The intraglandular differentiation is quite extensive; the differences in the pattern of gene activity between the anterior lobe and the main and side lobes are as great as between the salivary gland an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The K heterochromatin insertions were highly vacuolated. In contrast, the heterochroniatic centromere regions of the polytene Ss frequently exhibit distinct banding patterns (STAIBER and BEHNKE 1985). In an earlier investigation it was demonstrated that centromeric S bands contain sequences that could be activated to fomi a Balbiani ring when they are translocated into euchromatic chromosome sections (STAIBER 1982).…”
Section: Silver Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The K heterochromatin insertions were highly vacuolated. In contrast, the heterochroniatic centromere regions of the polytene Ss frequently exhibit distinct banding patterns (STAIBER and BEHNKE 1985). In an earlier investigation it was demonstrated that centromeric S bands contain sequences that could be activated to fomi a Balbiani ring when they are translocated into euchromatic chromosome sections (STAIBER 1982).…”
Section: Silver Stainingmentioning
confidence: 99%
“…2). In contrast to the Ks, each of the three Ss shows only one obvious centsomeric C-band, which corresponds to the large heterochromatic block representing the centromeric region in the polytene salivary gland chromosome (STAIBER and BEHNKE 1985). To facilitate the recognition of chromosomes and the comparison of banding patterns, a set of Gbanded Ks and Ss is shown in Fig.…”
Section: C-bandingmentioning
confidence: 99%
“…However, this approach is limited and less implemented in Malaysia. Polytene chromosomes are present in several dipteran tissues, including the salivary glands, malpighian tubules, and the epithelium of the midgut and hindgut [2,3]. There are several distinct characteristics which aid in classifying the group of chromosome arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Animals of a laboratory stock of Acricotopus lucidus (Diptera, Chironomidae) were used. Rearing conditions and development of the larvae were described earlier (16).…”
Section: Methodsmentioning
confidence: 99%